Urban solid waste in the production of Lafoensia pacari seedlings - Alan H. M. de Abreu; Leticia B. Marzola; Lucas A. de Melo; Paulo S. dos S. Leles; Elton L. S. Abel; Jorge M. Alonso (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to verify the potential of urban solid wastes as substrate for production of seedlings of Lafoensia pacari. Five treatments were tested, four with solid wastes and one standard substrate, namely: sewage sludge from Alegria Wastewater Treatment Plant (WTP); sewage sludge from Ilha do Governador WTP; sewage sludge from Sarapuí WTP; domestic garbage compost (Fertlurb); and a commercial substrate made of biostabilized pine bark (standard substrate). The wastes received 20% (in volume) of shredded coconut fiber. At 105 days after sowing, the seedlings were evaluated for different quality parameters. Seedlings produced with Sarapuí WTP sewage sludge showed the best results in all the parameters, followed by seedlings produced with sewage sludge from Alegria and Ilha do Governador WTPs, which did not differ. Seedlings produced with domestic garbage compost showed satisfactory results, higher than the ones observed for seedlings produced with commercial substrate. The urban solid wastes with 20% of coconut fiber showed high potential and can be recommended for the composition of substrate in the production of Lafoensia pacari seedlings.